Education in sport and physical activity future directions and global perspectives - Jong, Johan de; Petry, Karen (Routledge, 2022)
Sport and physical activity are embedded in our education systems and in wider society. This book takes the broadest possible look at this topic, across every key discipline and on different continents, opening up important new directions for the future development of sport and physical activity education. The book examines education in sport coaching, sport management, PE teacher training, physical activity and health promotion, and the emerging discipline of outdoor studies, considering how trends such as globalisation, digitalisation and privatisation are having a profound impact on education programs. It identifies some of the most important societal issues that must be addressed by sport and physical activity educators, including healthy lifestyles, inequality, intercultural aspects, human rights, and emerging technologies, and looks at how sport and physical activity education in Europe, North America, Latin America, Asia, and Australasia is evolving to meet these challenges. Designed to invite self-reflection, to provoke debate and to open up new cross-disciplinary and international perspectives within sports organisations and higher education institutions, this book is fascinating reading for advanced students, researchers, teachers and policy makers with an interest in sport and physical activity